Experience gained and difficulties in performing dynamic load test in composite piles made with steel rails - Bernardes, G. P.; Andreo, C. S.; Goncalves, C. (A A Balkema Publishers, 2000)
The results of dynamic instrumentation in two construction sites that used steel rails as pile foundation are presented in this paper. The first dynamic load tests were executed in piles made by single steel rails of the type TR32 and TR37. In the second group of dynamic tests, the piles were made by a composition of two and three steel rails of the same type TR37. The difficulties in placing the sensors, the effect of hammer blow eccentricity and the influence of the non-uniform welding along the pile length are presented in detail and discussed.